Social and Technological Transformation: A Literature Review on Learning Challenges in Elementary Schools - Fitra Imawarti; Sulastri; Mildayanti; Wa Ode Adelina; Wa Ode Siti Elma Sari; Aulia Nur Afifa Samiun; Muhammad Yusnan (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
he purpose of this study is to explore and understand the challenges faced in learning in primary schools in line with the ongoing social and technological transformation. This study uses a literature review method to explore the challenges of learning in primary schools in the context of social and technological transformation. This method involves collecting, assessing, and synthesizing relevant literature to gain a comprehensive understanding of the topic under study. By conducting a literature review, this study aims to identify patterns, findings, and gaps in the existing literature and provide valuable insights into the challenges and solutions in technology-based and social learning. The results of the study indicate that practical strategies and evidence-based recommendations to help educators overcome these challenges, such as inclusive approaches to reducing the digital divide and learning methodologies that utilize technology effectively. Thus, the results of this study are expected to provide comprehensive guidance to improve the quality of education in primary schools, as well as suggest policy and practice measures that can help education systems adapt to social and technological changes. The findings of the study will cover the impact of the digital divide, such as differences in access to technological devices and the internet between students, and how this affects equity in learning.